Laparoscopic partial adrenalectomy using near-infrared imaging: the initial experience. Issue 2 (1st April 2021) - Tuncel, Altug; Balci, Melih; Aykanat, Can; Aslan, Yilmaz; Berker, Dilek; Guzel, Ozer
Abstract: Introduction: To present our initial clinical experience with laparoscopic partial adrenalectomy using indocyanine green dye with near-infrared fluorescence imaging. Material and methods: A total of eight patients underwent transperitoneal laparoscopic partial adrenalectomy using indocyanine green dye with near-infrared fluorescence imaging in our clinic. After 5 mg intravenous indocyanine green dye administration, we resected the mass under the guidance of near-infrared fluorescence imaging and white light visualization in an effort to completely excise the mass while sparing uninvolved adrenal tissue. Results: Seven patients underwent unilateral and one patient underwent bilateral laparoscopic partial adrenalectomy. The median tumor size was 43 mm. The surgery was successfully performed with negative margins in all patients. The tumors were hypofluorescent relative to normal adrenal tissue with indocyanine green dye with near-infrared fluorescence imaging in patients with Cushing's syndrome, aldosteronoma, and adrenal cyst. However, pheochromocytoma and angiomyolipoma were noted to be isoflourorescent and hyperfluorescent relative to normal adrenal parenchyma, respectively. Conclusions: Laparoscopic partial adrenalectomy using intraoperative indocyanine green dye with near-infrared fluorescence imaging seems to be safe and feasible. This technology may ultimately be helpful in resecting lesions with more precise surgical margins by identifying the vascular structure during laparoscopic partial adrenalectomy. Abbreviations: LTA: Laparoscopic total adrenalectomy; LPA:Laparoscopic partial adrenalectomy; ICG: Indocynanine green; NIRF: Near-infrared fluorescence; HPA: Hypothalamic-pituitary-adrenal